Nuclear Donor Cell Lines Considerably Influence Cloning Efficiency and the Incidence of Large Offspring Syndrome in Bovine Somatic Cell Nuclear Transfer. Issue 4 (16th January 2013) - Liu, J; Wang, Y; Su, J; Luo, Y; Quan, F; Zhang, Y
Contents Total five ear skin fibroblast lines (named F1, F2, F3, F4 and F5) from different newborn Holstein cows have been used as nuclear donor cells for producing cloned cows by somatic cell nuclear transfer (SCNT). The effects of these cell lines on both in vitro and in vivo developmental rates of cloned embryos, post‐natal survivability and incidence of large offspring syndrome (LOS) were examined in this study. We found that the different cell lines possessed the same capacity to support pre‐implantation development of cloned embryos, the cleavage and blastocyst formation rates ranged from 80.2 ± 0.9 to 84.5 ± 2.5% and 28.5 ± 0.9 to 33.3 ± 1.4%, respectively. However, their capacities to support the in vivo development of SCNT embryos showed significant differences (p < 0.05). The pregnancy rates at 90 and 240 day were significantly lower in groups F2 (4.9% and 3.3%) and F3 (5.4% and 5.4%) compared to groups F1 (23.3% and 16.3%), F4 (25.7% and 18.6%) and F5 (25.9% and 19.8%) (p < 0.05). The cloning efficiency was significantly higher in group F5 than those in group F1, F2, F3 and F4 (9.3% vs 4.1%, 1.2%, 2.0% and 5.0%, respectively, p < 0.05). Moreover, large offspring syndrome (LOS) incidence in group F5 was significantly lower than those in other groups (p < 0.05). All cloned offspring from cell line F1, F2, F3 and F4 showed LOS and gestation length delay, while all cloned offspring from F5 showed normal birthweight and gestation length. We concluded that the nuclear donor cell lines have significant impact on the in vivo development of cloned embryos and the incidence of LOS in cloned calves.